IMPACT OF TOTAL QUALITY MANAGEMENT (TQM) IMPLEMENTATION ON SERVICE QUALITY AND PERFORMANCE OF ISLAMIC BANKS - Lisda Damai Yanti; Achmad Firdaus (Millah: Journal of Religious Studies, 2017)
Companies are competing to improve quality in the face of global market competition and so is Islamic banking industry. According to the Indonesian Islamic Banking Roadmap 2015-2019 issued by the Financial Services Authority (OJK), two out of the seven policies to be implemented are to improve service quality and product diversity, and to improve the quality and quantity of HR and IT. In any development of any industry, especially in the world of Islamic banking, the keys to improving competitiveness are companies’ service quality and performance. This research aims to analyze the effects of TQM implementation on service quality and performance of Islamic banks. Findings of this research show that TQM has a significant effect on service quality. Similarly, service quality has a significant effect on performance of Islamic banks as well. However, TQM has no direct significant effect on the performance of Islamic banks. –(Perusahaan berlomba-lomba untuk meningkatkan kualitas dalam menghadapi persaingan pasar global begitu juga dengan industri perbankan syariah. Pada Roadmap Perbankan Syariah Indonesia 2015-2019 yang di terbitkan oleh OJK, dua poin dari tujuh kebijakan yang akan dilaksanakan adalah memperbaiki kualitas layanan dan keragaman produk, serta memperbaiki kualitas dan kuantitas SDM & IT. Dalam setiap perkembangan industri apapun, terlebih dalam dunia perbankan syariah, kunci utama untuk meningkatkan daya saing adalah melalui kualitas layanan dan kinerja perusahaan. Penelitian bertujuan untuk menganalisis pengaruh penerapan TQM terhadap kualitas layanan dan kinerja bank syariah. Temuan penelitian menunjukan ada pengaruh yang signifikan antara TQM terhadap kualitas layanan. Demikian juga dengan kualitas layanan terhadap kinerja bank syariah terdapat pengaruh yang signifikan. Namun tidak ada pengaruh yang signifikan secara langsung antara TQM terhadap kinerja bank syariah.)-- Keywords: Total Quality Management, Service Quality, Performance of Islamic Banks, Structural Equation Modelling, and Partial Least Square